1998
DOI: 10.1046/j.1365-2486.1998.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal variation of carbon dioxide exchange from a former true raised bog

Abstract: Carbon dioxide exchange was measured, using the eddy covariance technique, during a one and a half year period in 1994 and 1995. The measurements took place over a former true raised bog, characterized by a shallow peat layer and a vegetation dominated by Molinia caerulea. The growing season extended from May until late October, with a maximum LAI in August of 1.7. The carbon balance shows a net release of 97 g C m–2 y–1 (265 kg C ha–1 y–1) from the peat bog ecosystem to the atmosphere. During June, July and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
7
36
0
Order By: Relevance
“…Conditions in the New Zealand experiment were very similar to those in the present experiment in that watertable depth ranged between 0.2 and 0.8 m (in our experiment between 0.4 and 0.8 m) and the vegetation at their site was a mixture of perennial ryegrass (Lolium perenne) and white clover (Trifolium repens). Other studies with water-logged conditions (Nieveen et al, 1998) report a lower R 10 of 1.3 µmol m -2 s -1 , indicating anaerobic conditions.…”
Section: Co 2 Emissionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Conditions in the New Zealand experiment were very similar to those in the present experiment in that watertable depth ranged between 0.2 and 0.8 m (in our experiment between 0.4 and 0.8 m) and the vegetation at their site was a mixture of perennial ryegrass (Lolium perenne) and white clover (Trifolium repens). Other studies with water-logged conditions (Nieveen et al, 1998) report a lower R 10 of 1.3 µmol m -2 s -1 , indicating anaerobic conditions.…”
Section: Co 2 Emissionsmentioning
confidence: 85%
“…When the temperature increased from 10 to 23°C, Moore and Dalva (1993) recorded a 2.3-fold increase in CO 2 emissions from peat soil in a laboratory experiment. Q 10 values (the Q 10 temperature coefficient is a measure of the rate of change of a biological or chemical system as a consequence of increasing the temperature by 10 °C) between 2 and 3 have been reported by Blodau (2002), but both smaller (Scanlon and Moore, 2000;Waddington et al, 2001) and larger Thurlow, 1996,1998;Nieveen et al, 1998) values have been reported. Many emission studies have been conducted on disturbed peat samples, without vegetation or under uncontrolled conditions in the field, as pointed out by Blodau et al (2004), but none on undisturbed soil with vegetation cover and under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…peat) are often found to be sources for carbon dioxide (Nieveen et al, 1998;Nieveen et al, 2005;Lloyd, 2006;Veenendaal et al, 2007), while grasslands on mineral soils (for example, clay and sand) often show a net uptake for carbon dioxide (Gilmanov et al, 2007). Clearly it can be observed that the Fochtelooërveen, Haastrecht, Oukoop and Stein sites follow this rule for organic soils and the Haarweg and Horstermeer sites for mineral soils.…”
Section: Respiration Characteristicsmentioning
confidence: 98%
“…CO 2 fluxes were measured between June 1994 and October 1995. More details about this site can be found in Nieveen et al (1998) and Jacobs et al (2003b).…”
Section: Fochtelooërveenmentioning
confidence: 99%
See 1 more Smart Citation